A new system to detect residual subgingival calculus: in vitro detection limits - Grit Meissner (journal of clinical periodontology, 2006)
Aim: We recently introduced an experimental surface detection system based on a conventional dental ultrasonic scaler. This device automatically discriminates cementum and dental calculus, which is the prerequisite for complete and thorough calculus removal. In the present study, the detection limits of this device were tested in vitro. Material and Methods: From 50 extracted teeth, subgingival calculus was gradually removed using a Gracey curette. During this stepwise procedure, detection properties of the surface detection system were continuously monitored and systematically verified until the system stopped discriminating calculus from the root surface. By measuring the diameter, circumference and area of the smallest, yet recognizable deposit, and of the no longer recognizable deposit, the cut-off point of the discriminative capability of the detection device was determined. Results: The cut-off points for the correct classification of residual deposits averaged on a diameter of 219 mm, an area of 21,600 mm2, and a circumference of 748 mm. This means a sensitivity of 73% and a specificity of 80% in this critical area. Conclusions: This calculus detection system was able to detect small deposits. In clinical practice, this device may support dentists in deciding whether to stop or to continue the debridement.